Role Play Technique to Improve Students' Speaking Skills - Henisah, Ratih; Margana, Margana; Putri, Reliska Yulita; Khan , Humaira Sharmin (International Journal of Contemporary Studies in Education, 2023)
Abstract: This study aims to investigate the use of role-play in teaching speaking skills and to improve the quality of teaching English to students who need to be addressed. This study focuses on implementing role play in the first grade of vocational high school pupils because it can make learning enjoyable and stress-free. Also, it is quite memorable. Implementing role play as a form of active learning will positively affect the success of instruction because it motivates students. Using this method to teach speaking aspects of a language results in students who are highly motivated and enthusiastic about learning the language. The data was gathered based on observation, interview and questionnaire survey. The steps involved in implementing the role-play method in a speaking class are as follows: determining the topic for discussion, selecting the situation and writing the dialogue, teaching the dialogue, rehearsing the dialogue, modifying the situation and dialogue, and presenting the dialogue in front of the class. According to research findings and expert opinions, role play effectively enhances students' speaking skills